A spatial model for evaluating the vulnerability of water management in Mexico City, Sao Paulo and Buenos Aires considering climate change. (March 2017) - Zambrano, Luis; Pacheco-Muñoz, Rodrigo; Fernández, Tania
Highlights: Water management in cities focuses on infrastructure for water supply and floods; but they must consider watershed dynamics. This paper presents a spatial model that evaluates land attributes at watershed scale for Mexico Buenos Aires and Sao Paulo. The model generates qualitative data without providing water balances, giving information to stakeholders of the watershed. Results suggest climate change has lower local impact than land use change, which reduces infiltration & increase flood risks. Natural areas are important for infiltration process and flood risk reduction, their protection is crucial on watershed resilience. Abstract: Water management in cities commonly focuses on reducing the risk of flooding and ensuring water supply by improving infrastructure locally. The supply of water and the process of flooding are directly related to the hydraulic dynamics of the watershed, however, and tools are lacking to evaluate and visualize hazards and solutions at the larger watershed scale. This paper presents a spatial model that evaluates the roles of water infiltration capacities and flood risks in watershed where cities are established. Understanding these characteristics is essential for managing water in urban areas, since water infiltration is related to the rainwater that may arrive to the aquifer, and floods are among the biggest concerns in risk management. We used spatial categorical data for land use, slope, soil texture, elevation, and precipitation to create a model that yields graded areas with different potential infiltration capacities, indicating susceptibility to flooding. The model can generate scenarios considering changes in land use and climate change up to the year 2050. We tested this model in Mexico City, Sao Paulo and Buenos Aires, three of the largest Latin American cities with different type of watersheds but similarities in population and policymaking. We found that climate change will decrease the infiltration capacities in Sao Paulo, but in the other two cities it will increase. Change in land use is the key factor, however, in reducing infiltration capacities and increasing the risk of flooding in all three cities. The model is applicable to urban areas in other parts of the world. These types of spatial models should be used in cities to emphasize the importance of watershed dynamics in managing water for the future.